2009
DOI: 10.1021/bi801859b
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Dithiol Glutaredoxin 8 from Saccharomyces cerevisiae: The Catalytic Redox Mechanism Redux

Abstract: Two dithiol glutaredoxins (Grxs), Grx1 and Grx2, from yeast have been characterized to date. A third putative dithiol glutaredoxin-encoding gene (GRX8) has been identified in silico. Here we show that deletion of GRX8 does not result in a reduced growth rate under oxidative stress conditions, nor does it enhance the defects of Deltagrx1 and Deltagrx2 single or double mutants. We furthermore compare the enzymatic properties of recombinant ScGrx8 with the monothiol glutaredoxin ScGrx7. Molecular models of ScGrx8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 59 publications
5
82
0
Order By: Relevance
“…They are found in different subcellular compartments including nuclear (Grx3/4), the mitochondrial matrix (Grx5), and the early secretory pathway (Grx6/7) (Rodriguez-Manzaneque et al 1999;Molina et al 2004;Izquierdo et al 2008;Mesecke et al 2008;Eckers et al 2009). Grx3/4 play an essential role in intracellular iron trafficking (Muhlenhoff et al 2010) and Grx5 is required for mitochondrial [4Fe-4S] cluster assembly (Rodriguez-Manzaneque et al 2002).…”
Section: Antioxidant Defensesmentioning
confidence: 99%
“…They are found in different subcellular compartments including nuclear (Grx3/4), the mitochondrial matrix (Grx5), and the early secretory pathway (Grx6/7) (Rodriguez-Manzaneque et al 1999;Molina et al 2004;Izquierdo et al 2008;Mesecke et al 2008;Eckers et al 2009). Grx3/4 play an essential role in intracellular iron trafficking (Muhlenhoff et al 2010) and Grx5 is required for mitochondrial [4Fe-4S] cluster assembly (Rodriguez-Manzaneque et al 2002).…”
Section: Antioxidant Defensesmentioning
confidence: 99%
“…The dithiol GRXs Grx1p and Grx2p (CPYC active site) are mainly cytosolic, but a minor portion of Grx2p is located within mitochondria (Luikenhuis et al, 1998;Porras et al, 2006). Despite the proposed role of Grx1p and Grx2p as general thiol oxidoreductases, their absence causes only moderate hypersensitivity to superoxide (in the case of Grx1p) and to superoxide and hydroperoxide (in the case of Grx2p) (Eckers et al, 2009;Luikenhuis et al, 1998). This phenotype could be explained based on the activity of these GRXs as glutathione peroxidases in in vitro assays (Collinson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They have a singlecysteine active site, but their amino acid sequences are more similar to dithiol GRXs. Finally, Grx8p is a cytoplasmic dithiol enzyme with a non-standard CPDC active site and low activity in vitro (Eckers et al, 2009). Its absence does not cause significant growth phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, no significant activity was detected for the Clot proteins, either from poplar or Arabidopsis (data not shown). The orthologs from S. cerevisiae (also referred to as ScGrx8) or from mammals (referred to as TRP14), which possess the same active site, are also not able or are very poorly able to reduce insulin, and a faint activity in the HED assay was detected for ScGrx8 (Jeong et al, 2004;Eckers et al, 2009). However, it has been shown that TRP14 can reduce a disulfide in the dynein light chain LC8, contributing to the inhibitory activity of LC8 toward the nuclear factor kB (Jung et al, 2008).…”
mentioning
confidence: 99%